2014
DOI: 10.1097/qco.0000000000000049
|View full text |Cite
|
Sign up to set email alerts
|

What role do viruses play in nosocomial pneumonia?

Abstract: Respiratory viruses are mainly responsible for CAP, but they may also cause healthcare-associated pneumonia. HSV bronchopneumonitis and cytomegalovirus pneumonia are not rare diseases, and patients with Herpesviridae lung infections have worse prognoses than those without. Whether or not those Herpesviridae infections are responsible for true morbidity or morbidity remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 48 publications
0
26
0
1
Order By: Relevance
“…Residing latently in sensory neurons, HSV reactivates in states of reduced immunocompetence [2]. Several studies have shown that HSV-1 reactivation and active replication in the respiratory tract are common in mechanically ventilated intensive care unit (ICU) patients even without underlying immunosuppression, with reported rates of 5 to 64% [3]. Ong et al, in the largest study available to date, detected active HSV replication in 27% of 393 ventilated ICU patients, which was associated with a nearly twofold increase in hospital mortality (41% vs 24%, p = 0.002) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Residing latently in sensory neurons, HSV reactivates in states of reduced immunocompetence [2]. Several studies have shown that HSV-1 reactivation and active replication in the respiratory tract are common in mechanically ventilated intensive care unit (ICU) patients even without underlying immunosuppression, with reported rates of 5 to 64% [3]. Ong et al, in the largest study available to date, detected active HSV replication in 27% of 393 ventilated ICU patients, which was associated with a nearly twofold increase in hospital mortality (41% vs 24%, p = 0.002) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Viruses play important roles in respiratory tract infections. [1][2][3][4] Recently, several novel respiratory viruses have emerged, including the 2009 pandemic influenza virus A(H1N1)pdm09, 5 the avian influenza viruses A(H7N9) and A(H5N6), [6][7][8] and the Middle East Respiratory Syndrome (MERS) coronavirus. 9 The novel avian influenza viruses and the MERS coronavirus are associated with high mortality rates of over 30%.…”
Section: Introductionmentioning
confidence: 99%
“…Along with recent advantages in diagnosis (6), new challenges have occurred in the management of viral infections (true disease versus colonization), especially among high risk patients (such as immunocompromised hosts). Also, there are limited data regarding the clinical importance of isolated virus (such as HHVs) in lower respiratory tract of critically ill individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary viral infections (primary or reactivation) (6,11,12) may be accompanied by susceptibility to certain bacterial or fungal infections (4,13,14) and further complications (15)(16)(17). time of reactivation, the virus may be excreted through the respiratory and digestive tract (17).…”
Section: Introductionmentioning
confidence: 99%